Excess Thermodynamic Properties of Binary Mixtures of Dimethyl Malonate with some Branched Alkanols - Krishna, K. P.; Sandhyasri, P. B.; Anitha, K.; Babu, G. R.; Kumar, K. R.; Raju, R. R. (Journal of Scientific Research, 2022)
The intermolecular hydrogen bond interactions in the dimethyl malonate with some branched alkanols (2-methyl-1-propanol, 2-propanol, and 2-butanol) binary mixture have been studied experimentally and theoretically. The ultrasonic velocities U, densities ρ of binary mixtures of dimethyl malonate with 2-methyl-1-propanol, 2-propanol, 2-butanol from 303.15 K to 318.15 K were measured. Excess molar volume (VE), deviation in adiabatic compressibility (Δβad) and excess intermolecular free length ( LEf) have been calculated from the measured experimental data. It is observed that the order of interactions in dimethyl malonate – branched alkanols mixtures is 2-methyl-1-propanol > 2-propanol > 2-butanol.